PagSOD2a improves poplar salt tolerance by elevating superoxide dismutase activity and decreasing malondialdehyde contents - Zhou, Lieding; Yu, Changhong; Nan, Siyuan; Li, Yajing; Hu, Jia; Zhao, Kai; Guo, Jinping; Wang, Shengji (Frontiers in Plant Science, 2024)
Superoxide dismutase (SOD) is widely present in plants and plays a crucial role in defending against oxidative stress and preventing tissue damage. This study discovered that the PagSOD2a gene in 84K poplar (Populus alba × P. glandulosa) exhibits a distinct capacity to be induced in response to salt stress. To delve into the pivotal role of PagSOD2a in conferring salt tolerance, the entire PagSOD2a fragment was successfully cloned from 84K poplar and the potential function of PagSOD2a was explored using bioinformatics and subcellular localization. PagSOD2a was found to encode a CuZn-SOD protein localized in chloroplasts. Furthermore, six CuZn-SOD family members were identified in poplar, with closely related members displaying similar gene structures, indicating evolutionary conservation. Morphological and physiological indexes of transgenic 84K poplar overexpressing PagSOD2a (OE) were compared with non-transgenic wild-type (WT) plants under salt stress. The OE lines (OE1 and OE3) showed improved growth performance, characterized by increased plant height and fresh weight, along with reduced malondialdehyde (MDA) content and electrolyte leakage rate under salt stress. Meanwhile, overexpression of PagSOD2a significantly augmented CuZn-SOD and total SOD enzyme activities, leading to a reduction in superoxide anion accumulation and an enhancement of salt tolerance. Additionally, co-expression and multilayered hierarchical gene regulatory network (ML-hGRN) mediated by PagSOD2a constructed using transcriptome data revealed that PagSOD2a gene may be directly regulated by SPL13, NGA1b and FRS5, as well as indirectly regulated by MYB102 and WRKY6, in response to salt stress. These findings provide a theoretical and material foundation for further elucidating the function of PagSOD2a under salt stress and for developing salt-tolerant poplar varieties.